PS02.180: THE ROLE OF CARDIOPULMONARY EXERCISE TESTING IN OESOPHAGO-GASTRIC CANCER SURGERY: EVALUATION OF A SINGLE-CENTRE EXPERIENCE. (14th September 2018) - Allen, Sophie; Chakravartty, Saurav; Timbrell, David; Rockall, Timothy; Prabhu, Pradeep; Preston, Shaun; Sultan, Javed
Abstract: Background: Cardiopulmonary exercise testing (CPEX) is an objective measure of functional capacity adapted to predict post-operative morbidity. CPEX may also identify optimisable cardio-respiratory comorbidity, prompting treatment modification or specialist referral. The role of CPEX in patient optimisation before oesophago-gastrectomy is yet to be evaluated. This study aims to assess the utility of CPEX in altering management and optimising patients prior to oesophago-gastrectomy. Methods: All patients who underwent pre-operative CPEX testing and two phase oesophago-gastrectomy (January 2012 to January 2018) were included. All changes in patient management brought about by CPEX findings were evaluated. In addition, the role of validated risk-stratifying CPEX parameters (anaerobic threshold (AT), VO2 peak and FEV1) in predicting post-operative complications was assessed. Results: 236 patients underwent surgery. Median AT and VO2 peak were 11.95(7–24)ml/kg/min and 773(403–1552)ml/min/m 2 respectively. 46% (109/236) of patients (VO2 peak > 800ml/min/m 2 ) were graded 'low risk', 42% (99/236) 'intermediate risk' (VO2 peak = 600–800ml/min/m 2 ), and 12% (28/236) 'high risk' (VO2 peak < 600ml/min/m 2 ) for developing post-operative cardio-pulmonary complications. Based on CPEX findings, management plans were altered in 84 patients (36%). Cardiac comorbidity was identified in 55 patients (23%) with immediate alteration of cardiac medications in 9% (21/236) and another 11% (27/236) requiring specialist cardiology review. Medication for respiratory optimisation was initiated in 3% (7/236) and formal respiratory review sought in 5% (12/236). 'Intermediate' and 'high risk' patients had similar rates of overall complication (63% vs 63%, P = 1.00), cardio-pulmonary complication (48% vs 47%, P = 0.17), anastomotic leak (11% vs 15%, P = 0.33) and 90-day mortality (6% vs 4%, P = 0.40) compared with 'low risk' groups. CPEX variables (AT, VO2 peak, FEV1) did not predict complications, length of critical care or overall stay on Receiver Operating Characteristic curves (AUROC < 0.5) and multivariate logistic regression models. Conclusion: CPEX findings changed management in 36% of patients, enabling optimisation before oesophago-gastrectomy. 'Confounding by intention' is a bias reducing the strength of association between test results and post-operative complications due to the propensity to medically intervene on the basis of the test findings. This study highlights the possibility that the high intervention rate may explain the poor correlation between test results and post-operative outcome. Disclosure: All authors have declared no conflicts of interest.